Finite element method for beam bending problem - Abdullah Sani, Sarah A'Fifah (2012)
Previously in Yavari A. et. al. (2000), the beam bending problem having various jump discontinuities was solved using an exact technique known as the auxiliary beam method. Our work continue the effort by formulating solution for the displacements and slopes of nodes under three different situations of the beam, namely, clamped, simply-supported beam, clamped-clamped beam, and simply-supported beam. A manual solution has been proposed to solve this problem. We deploy the finite element method. In the first step, the main component is solved to obtain the stiffness matrix. Next, the load vector and the boundary vector are computed to complete the solution. The solutions are computed and verified using MAPLE.